2006
DOI: 10.1038/sj.jhh.1002003
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertension with single nucleotide polymorphisms in the quantitative trait locus for abdominal obesity-metabolic syndrome on chromosome 17

Abstract: Genome scan in Chinese revealed an association of blood pressure with the microsatellite marker D17S1303, which lies in a quantitative trait locus for the abdominal obesity-metabolic syndrome (AOMS2) at 17p12 on chromosome 17. We previously reported that D17S1303 was associated with hypertension and obesity. Therefore, we studied 10 single nucleotide polymorphisms (SNP) within 3 kb of D17S1303. One hundred and eighty hypertensive subjects (91 men, 89 women, age 53712 years) and 180 normotensive matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The present results are compatible with our previous findings, 4,5 suggesting that an unidentified gene or a regulatory element influencing the development of hypertension may be found in a region downstream of the microsatellite marker D17S1303. The number of subjects with new onset hypertension was limited, so the sample size or the length of follow-up needs to be increased in future.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…The present results are compatible with our previous findings, 4,5 suggesting that an unidentified gene or a regulatory element influencing the development of hypertension may be found in a region downstream of the microsatellite marker D17S1303. The number of subjects with new onset hypertension was limited, so the sample size or the length of follow-up needs to be increased in future.…”
supporting
confidence: 93%
“…4 Some single nucleotide polymorphisms (SNPs) within a 3 kb region of D17S1303 were associated with hypertension in a case-control study. 5 A recent genome-wide linkage analysis for blood pressure also revealed an association of the microsatellite marker, D17S921 at 17p12 (about 4000 kb downstream from D17S1303) with diastolic blood pressure in pooled Australian and Dutch populations. 6 Therefore, there may be an unidentified gene or regulatory element in the vicinity of this locus that determines blood pressure.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…17 This could potentially lead to the development of new drugs that could target both hypertension and the metabolic syndrome. 18 Also, Guizar-Mendoza et al 19 performed a study to establish the relationship between Gln223Arg polymorphism in the human leptin receptor gene (LEPR) and traits related to obesity in Mexican adolescents. Their study showed that obese adolescents have higher heart sympathetic activity, blood pressure, insulin and leptin levels than non-obese subjects, and furthermore those who were carriers of the Gln223Arg polymorphism of LEPR have sympathetic overactivity and hypertension.…”
mentioning
confidence: 99%